PENJAGAAN KESEHATAN MENTAL DALAM TAFSIR AL-JAILANI KARYA SYEKH ABDUL QADIR AL-JAILANI - Rofiqul, Iskandar (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2025)
Mental health is a fundamental aspect of human well-being that integrates physical, emotional, social, and spiritual dimensions. In Islam, the Qur'an serves not only as a legal reference but also as a guide to achieving inner balance and spiritual resilience. This study explores the paradigm, foundation, and indicators of mental health based on Tafsir Al-Jailani by Shaykh Abdul Qadir Al-Jailani. The analysis employs a thematic and Sufi-exegetical approach focusing on four central verses: QS. Ar-Ra’d: 28, QS. Al-Baqarah: 153 and 155, and QS. Yunus: 57. The findings reveal that Islamic mental health is rooted in the concept of tawḥīd dhātī (the essential oneness of God) as an ontological and existential foundation of spiritual awareness. Dhikr (remembrance of God) is interpreted not merely as verbal worship, but as an inner consciousness that brings peace and emotional stability. Patience (ṣabr) and prayer (ṣalāh) serve as spiritual-regulatory mechanisms for navigating life’s hardships. The Qur’an, particularly as interpreted in QS. Yunus: 57, functions as admonition (maw‘iẓah), healing (shifā’), guidance (hudā), and mercy (raḥmah), providing therapeutic value for inner afflictions. This study concludes that Qur’anic mental health is not merely the absence of psychological disorders, but rather a state of inner tranquility (iṭmi’nān), existential stability, and a strong vertical connection with God. Indicators of such mental health include serenity of the heart, perseverance, spiritual connectivity, receptiveness to divine counsel, and emotional equilibrium. Thus, Tafsir Al-Jailani offers a rich foundation for developing a spiritually grounded Islamic psychological framework applicable to both individual and communal life. Keywords: Shaykh Abdul Qadir Al-Jailani, Tafsir Al-Jailani, mental health, tawḥīd dhātī, dhikr, patience, spirituality, Islamic psychology